Implementation Of Sharia Economic Principles In Micro, Small And Medium Enterprises - Muhammad Fakhri Khairi; Khoirudin; MHD. Nanang Hidayat; M.Ilham (LP2M IAIN Palopo, 2026)
This study aims to analyze the implementation of sharia economic principles in Micro, Small, and Medium Enterprises (MSMEs) and its impact on business management and economic performance based on a literature review. The approach used is a literature review by examining various scientific journals discussing the application of sharia values in MSME practices. The data used is secondary data from relevant previous research results, which are then analyzed descriptively and analytically to identify implementation patterns, impacts, and research gaps. The results of the study indicate that the implementation of sharia economic principles in MSMEs is reflected in fair and honest transaction practices, a riba-free financing system with clear contracts, transparent and accountable financial management, and strengthening the social dimension through cooperation and business ethics. The application of these principles has a positive impact on the quality of business governance, improved managerial discipline, capital structure stability, better risk management, and increased consumer trust and loyalty. Economically, sharia values contribute to business sustainability and the expansion of market opportunities, including through the use of digital media that maintains ethical transactions. However, the literature also indicates research gaps such as the dominance of local case studies, the lack of quantitative measurements of economic impact, and limited studies on the integration of sharia principles with digital and financial technology. This research confirms that the principles of Islamic economics not only serve as moral guidelines but also as a strategy for strengthening fair, resilient, and sustainable MSMEs in facing the dynamics of the modern economy.